PENINGKATAN KOMPETENSI GURU SD MELALUI PENGEMBANGAN MEDIA BELAJAR INTERAKTIF MENGGUNAKAN GOOGLE WORKSPACE FOR EDUCATION - Muhammad Iqbal Fawwaz; Muhammad Fikri Akbar; Madziatul Churiyah; Sholikhan (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2023)
Indonesia has witnessed significant developments in its education system. However, challenges persist, including the limited use of interactive and innovative teaching methods at the primary school level. In the field, particularly in Gugus 5 Blimbing, many teachers lack the competence to develop interactive and innovative teaching materials. Leveraging Google Workspace for Education, this initiative aims to empower educators with accessible tools. The project entails three key activities: 1) Providing primary school teachers in Gugus 5 Blimbing with guidelines for creating interactive teaching materials; 2) Hosting a workshop on "Developing Teaching Materials for Primary School Teachers Using Google Workspace for Education and Tome AI"; and 3) Producing video tutorials on "Enhancing Teaching Materials for Primary School Teachers with Google Workspace for Education and Tome AI". This endeavor seeks to enable teachers to create more engaging and interactive learning experiences, ultimately improving student outcomes and the overall quality of primary education in Indonesia.